Woodburn Grange: A story of English country life; vol. 2 of 3 - Howitt, William, 1792-1879 (Salt Lake City, UT : Project Gutenberg, 2022)
"Woodburn Grange: A Story of English Country Life; vol. 2 of 3" by William Howitt is a novel written in the mid-19th century. The story unfolds in a pastoral English backdrop, detailing the lives, relationships, and moral dilemmas of its characters, particularly focusing on the poignant love story between Ann Woodburn and Henry Clavering, as well as the intricate details of social dynamics in their community. This volume continues to explore themes of faith, duty, and the complexities of love as the characters navigate their evolving relationships and the societal expectations that govern them. At the start of the narrative, we see a conversation among the women of Woodburn Grange reflecting on the return of Henry Clavering, who is held in high regard by the Woodburn family. However, beneath the surface, Ann struggles with her feelings for him, primarily due to his lack of faith in Christianity, which she views as a significant incompatibility for a future together. As their interactions unfold, the tension between personal desires and moral beliefs becomes increasingly evident. This introduction sets the stage for deeper explorations of the characters$1 (Brelationships and conflicts, highlighting a blend of romance, societal critique, and the tension between faith and doubt. The volume hints at an interconnected web of relationships that will unravel as the characters confront their hearts' desires amidst their ethical and familial obligations. (This is an automatically generated summary.)s
Release date is 2022-12-26
Sonya Schermann, Bob Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Religious fiction